2003
DOI: 10.1038/sj.npp.1300259
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Assessment of Ethological and Dopamine Receptor Agonist-Induced Behavioral Phenotype in Mutants with Congenic DARPP-32 ‘Knockout’

Abstract: Congenic (10 backcrosses into C57BL/6J) mutants with targeted gene deletion of DARPP-32, a neuronal phosphoprotein regarded as an essential mediator of the biological effects of dopamine (DA), were assessed phenotypically using an ethologically based approach that resolves all topographies of behavior in the mouse repertoire. Over initial exploration, female, but not male, DARPP-32 mutants evidenced increased locomotion and decreased grooming, while a decrease in rearing seated was evident in mutants of both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…In initial studies with dopaminergic agents, the acute stimulatory response to the nonselective, indirect dopaminergic agonist amphetamine, and catalepsy induced by lower but not higher doses of the antipsychotic raclopride, seemed reduced in DARPP-32 mutants (Fienberg and Greengard, 2000;Svenningsson et al, 2003). In our own studies (Nally et al, 2003), we reported ethologically based alterations in the topography of behavioral responsivity to the nonselective dopamine receptor agonist apomorphine in DARPP-32 mutants. However, the role of DARPP-32 in mediating distinct topographies of D 2 -like-mediated behavior, as induced by selective stimulation of D 2 -like receptors and attenuated by selective antagonism thereof, remains to be clarified.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…In initial studies with dopaminergic agents, the acute stimulatory response to the nonselective, indirect dopaminergic agonist amphetamine, and catalepsy induced by lower but not higher doses of the antipsychotic raclopride, seemed reduced in DARPP-32 mutants (Fienberg and Greengard, 2000;Svenningsson et al, 2003). In our own studies (Nally et al, 2003), we reported ethologically based alterations in the topography of behavioral responsivity to the nonselective dopamine receptor agonist apomorphine in DARPP-32 mutants. However, the role of DARPP-32 in mediating distinct topographies of D 2 -like-mediated behavior, as induced by selective stimulation of D 2 -like receptors and attenuated by selective antagonism thereof, remains to be clarified.…”
mentioning
confidence: 80%
“…On this basis, we have recently studied congenic DARPP-32 mutants at an ethological level, with the resultant ethogram revealing only subtle phenotypic effects at the level of spontaneous behavior (Nally et al, 2003). In initial studies with dopaminergic agents, the acute stimulatory response to the nonselective, indirect dopaminergic agonist amphetamine, and catalepsy induced by lower but not higher doses of the antipsychotic raclopride, seemed reduced in DARPP-32 mutants (Fienberg and Greengard, 2000;Svenningsson et al, 2003).…”
mentioning
confidence: 99%
“…No statistically significant differences were found in gait analysis or rotarod testing in MUT mice examined at 10-11 or 17-21 wk (SI Text). Separate cohorts of WT and MUT animals were assessed at two different age ranges by using a standardized ethological assay (22)(23)(24). At 6-9 wk, there was an increase in total rearing and a decrease in sifting and chewing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Topographical responses to A 68930 were unaltered, with an effect of genotype in the absence of any dose × genotype interaction indicating an overall increase in horizontal jaw movements in DARPP-32 mutants that was unrelated to treatment; this echoes a similar increase in general topographies of behaviour in DARPP-32 mutants that we have reported previously using an ethologically based paradigm, and which may reflect a subtle action of the stress of the injection procedure to reveal phenotypic effects not present under other conditions (Nally et al, 2003(Nally et al, , 2004.…”
Section: Discussionmentioning
confidence: 53%
“…and analysed using repeated-measures analysis of variance (ANOVA) after square-root transformation in the absence of appropriate non-parametric techniques; univariate comparisons were made where overall effects on ANOVA were significant, using Student's t-test or Mann-Whitney U-test after Kruskal-Wallis analysis as appropriate Ross et al, 2000;Tomiyama et al, 2001Tomiyama et al, , 2002Tomiyama et al, , 2004Makihara et al, 2004;Nally et al, 2003Nally et al, , 2004O'Sullivan et al, 2004O'Sullivan et al, , 2005. Fienberg et al, 1998;Nally et al, 2003Nally et al, , 2004.…”
Section: Discussionmentioning
confidence: 99%